COVID-19 among LGBTQ+ individuals living with HIV/AIDS: psycho-social challenges and care options - Aditi Tomar; Mandy N Spadine; Taylor Graves-Boswell; Lisa T Wigfall (AIMS Press, 2021)
Prolonged social isolation during the COVID-19 lockdown has adversely impacted the mental, social, and physical wellbeing of the global populace. Coping with mental and physical stressors amidst the global lockdown is especially strenuous for the Lesbian, Gay, Bisexual, Transgender, and more (LGBT+) community, who are frequently subjected to social stigma and minority stress. Systematic stigma and discrimination place LGBT+ individuals at higher risk for deleterious behaviors, such as substance abuse (e.g., injection drug use, smoking, alcohol) and risky sexual practices (e.g., anal/vaginal/oral sex). Maladaptive coping behaviors consequently increase the chances of HIV/AIDS risk among LGBT+ individuals, compared to heterosexual individuals. LGBT+ individuals Living with HIV/AIDS perpetually face higher rates of unemployment, income disparity, and intimate partner violence. Prolonged home confinement, and impaired accessibility to healthcare, legal, and criminal justice services during lockdown may deplete the quality of life of LGBT+ individuals Living with HIV/AIDS. Therefore, it is critical that multidisciplinary service providers, including health professionals, employers, social services providers, educational institutions and community organizations, move toward online service delivery, so that homebound HIV-positive LGBT+ individuals are secured with a wide range of care options. Non-judgemental, tele-counseling may bridge the gap to mental health services. Community clinics catering to HIV-positive and/or LGBT+ clients may consider precociously supplying essential amenities, such as Preexposure (PrEP)/postexposure prophylaxis (PEP), condoms, emergency contraception, and sterile needles. Lastly, efforts directed at the sustenance of at-risk/HIV-positive LGBT+ health should persevere, even after the pandemic.